Determinants of clinical presentation on outcomes in older patients with myocardial infarction. Issue 12 (11th October 2018) - Breining, Alice; Negers, Antonin; Mora, Lucie; Moïsi, Laura; Golmard, Jean L; Cohen, Ariel; Verny, Marc; Collet, Jean P; Boddaert, Jacques
Abstract : Aim: Myocardial infarction without chest pain misleads the clinician, resulting in a diagnosis delay and an increase of mortality. The main objective of the present study was to determine the risk factors of atypical presentation in older patients with myocardial infarction. Methods: All consecutive patients aged ≥75 years presenting with myocardial infarction and hospitalized in the cardiology intensive care unit were included in the present prospective multicenter observational study. All patients benefited from both specialized cardiac management and geriatric assessment. Results: A total of 215 consecutive patients were included. The mean age was 85 ± 6 years. A total of 142 patients (66%) had a typical presentation (i.e. chest pain) and 73 patients (34%) had an atypical clinical presentation (i.e. no chest pain). A total of 29 (13.5%) patients died within 30 days of the index hospitalization. Higher Cumulative Illness Rating Score‐Geriatric severity index score ( P  = 0.019) and initial atrial fibrillation ( P  = 0.022) were predictive of 30‐day all‐cause mortality. Typical presentation ( P  = 0.010) was a protective factor of 30‐day all‐cause mortality. A Cumulative Illness Rating Score for Geriatrics total score increase ( P  = 0.0003) and residing in a nursing home ( P  = 0.024) emerged as independent risk factors for atypical presentation. Conclusions: In "real‐life" elderly patients, comorbidities influence the prognosis of myocardial infarction, but also clinical presentation. Identification of patients at risk of atypical presentation; that is, patients with multiple comorbid conditions, might help refine the prognostic value in older patients with myocardial infarction.Geriatr Gerontol Int 2018; 18: 1591–1596 .